Comparative study of phenotypic-based detection assays for carbapenemase-producing Acinetobacter baumannii with a proposed algorithm in resource-limited settings. - Piyatip Khuntayaporn (Public Library of Science (PLoS), 2021)
The increasing incidence of carbapenem resistance in Acinetobacter baumannii is a critical concern worldwide owing to the limitations of therapeutic alternatives. The most important carbapenem resistance mechanism for A. baumannii is the enzymatic hydrolysis mediated by carbapenemases, mostly OXA-type carbapenemases (class D) and, to a lesser extent, metallo-β-lactamases (class B). Therefore, early and accurate detection of carbapenemase-producing A. baumannii is required to achieve the therapeutic efficacy of such infections. Many methods for carbapenemase detection have been proposed as effective tests for A. baumannii; however, none of them are officially recommended. In this study, three carbapenemase detection methods, namely, CarbaAcineto NP test, modified carbapenem inactivation method (mCIM), and simplified carbapenem inactivation method (sCIM) were evaluated for phenotypic detection of clinically isolated A. baumannii. The MICs of imipenem, meropenem, and doripenem were determined for 123 clinically isolated A. baumannii strains before performing three phenotypic detections. The overall sensitivity and specificity values were 89.09%/100% for the carbAcineto NP test, 71.82%/100% for sCIM, and 32.73%/33.13% for mCIM. CarbAcineto NP test and sCIM performed excellently (100% sensitivity) when both Class B and Class D carbapenemases were present in the same isolate. Based on the results, the combined detection method of sCIM and CarbAcineto NP test was proposed to detect carbapenemase-producing A. baumannii rather than a single assay, significantly increasing the sensitivity of detection to 98.18%. The proposed algorithm was more reliable and cost-effective than the CarbAcineto NP test alone. It can be easily applied in routine microbiology laboratories for developing countries with limited resources.